Ignatian Redarquia: Leadership for the 21st Century (Journal of Parents and Teachers, 2023)
In an ever-changing world, in the age of collaboration, we cannot and should not afford hierarchical leadership in our schools. We must demand of ourselves the adoption of processes, policies and structures that promote, maintain and do not contradict the principles and values for and in which we educate. It is in this direction that our Ignatian redarchy is heading: to facilitate structures and relationships of shared action, to live meaningfully and fully with and for others.
Keywords: leadership; Society of Jesus; collaboration; participation; global citizenship